Homonymous hemianopsia as the leading symptom of a tumor like demyelinating lesion: a case report - Evangelopoulos, Maria Eleptheria (BioMed Central, 2009)
INTRODUCTION: Differential diagnosis of a cerebral lesion can prove to be a very challenging task for the treating physician. Many non-neoplastic neurological diseases can mimic brain neoplasms on neuroimaging. CASE PRESENTATION: A previously healthy 23-year-old male, presented with blurred vision to the Emergency Department of our Hospital. After initial clinical and serological examination, he was admitted to our clinic for further investigation. Neurological examination showed left homonymous hemianopsia. Brain MRI revealed edema of the right parietal lobe, compressing the posterior region of the right ventricle. Serum viral, immunological and paraneoplasmatic testing were negative. Spectroscopic MRI described the lesions as tumefactive demyelinated plaques. After treating the patient with intravenous corticosteroids, his symptoms rapidly improved and the extensive lesion of the parietal lobe decreased. CONCLUSION: In case of young patients with tumor-like lesions, demyelination should always be considered in the differential diagnosis.